Male attitudes to female dundun drumming in western Nigeria (2014)
Although dundun drumming has been a stereotypically male-dominated profession, female dundun drumming is emerging as an established musical art form among the Yoruba of south-western Nigeria. This paper examines the perception and attitude of Yoruba male drummers to this relatively new development. In-depth interviews and focus group discussions were used to collect data from dundun master drummers in selected Yoruba towns and cities. Two divergent viewpoints were expressed by the male drummers. The liberal ones have not only accepted change, but have also given due recognition to female dundun drummers as colleagues and partners in progress. The other group — hardliners and sustainers of stereotypical traditional roles — however cited spiritual and physical reasons, such as taboos and the non-admittance of women into arenas where cultic activities take place, as well as physical inadequacy and lack of stamina due to the rigorous nature of drumming for their nonrecognition of female drummers. Besides the fact that the physiological make up of women makes the carriage and playing position of the drum inconvenient, this paper argues that drumming is a profession for both men and women. Also, the success stories of some popular female dundun artistes appear to mirror the shifting paradigm in the societal perception of professions in relation to gender.